An Orthogonal-based Self-starting Numerical Integrator for Second Order Initial and Boundary Value Problems ODEs; Journal of Physics: Conference Series; Vol. 1145 : Prospects of Fundamental Sciences Development (PFSD-2018) - Mohammed U. (2019, 2019)
Title screen